Research Activities in the Modern Educational Environment - Aminovich, Ikramov Amirbek (European Journal of Life Safety and Stability (2660-9630), 2022)
the article substantiates the relevance of research activities in the modern educational environment, analyzes the basic principles of the organization of research work of students, and considers the main stages of research work as a joint activity of the student and the teacher.